Shadowing research in organizations: the methodological debates. (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to provide some context for the special issue and to introduce the collection of invited commentaries and research papers that follow. It also sets out to clarify the contribution that shadowing methods can make to the study of organizations.Design/methodology/approach – This is done by briefly outlining the ways in which shadowing methods have developed in parallel within a number of disciplines. In order to tackle the question of why this has happened, a grounded approach is taken which centres on data excerpts generated by a shadowing method and three of its closest methodological neighbours: interviews, observation and participant observation. The paper further develops this analysis through the presentation of a set of illustrative analogies which use the idea of the researcher's gaze as a beam of light.Findings – Similarities and differences between shadowing, interviews, observation and participant observation are identified, which support the articulation of shadowing as a family of following methods.Research limitations/implications – Taken together, the contributions from the invited commentaries and research papers, suggest a number of ways in which the debate surrounding shadowing research in organizations needs to be developed going forward.Originality/value – The reflexive, comparative methodological approach taken here provides for the first time a systematic comparison of shadowing in relation to other common qualitative data elicitation methods. Further, the development of a critique of the extant literature on shadowing provides a basis on which to progress the field, both in terms of shadowing practices themselves and writing about them within disciplines and across the research methods literature.